Evaluation of storage of sunflower pellets in silo bags - Behr, Enrique Federico (2021)
Silo bags are a temporary and potentially hermetic storage system widely used for grains, oil seeds, legumes and other products. Oil extraction of sunflower seeds through the extrusion expelling process generates a high protein sub product, which is pelletized for animalconsumption. Storing sunflower pellets in silo bags could bring logistical advantages to animalproduction farms and the sunflower processing industry. Thus, the objectives of this work were to: 1) study the effect of silo bag storage on chemical composition and fungal biota evolution on sunflower pellets; and 2) quantify the mechanical damage due to the loading and unloading operation on pellet stability. The study was carried out in a facility near Crespo (Entre Rios Province, Argentina), between February and October of 2018. Samples were collected during the loading (initial) and unloading (final) of the pellets to/from the silo bag. Samples were analyzed for fungal biota, mycotoxins, and composition (moisture content, protein, fat, and fiber). Temperature, relative humidity and CO2 concentration were measured during storage. Mechanical damage was evaluated by measuring pellet length and dust percentage. Storage moisture content was around 9% (dry basis) and did not change during storage, while relative humidity remained below 60%. The evolution of CO2 concentration was related to the pellet temperature inside the bag (summer time 14.3% CO2 and 30°C, winter time 6.0% CO2 and 15.3°C). Fungal colony counts in the initial samples were low (1.2x101 CFU/g DM) and slightly increased during storage (3.4x102 CFU/g DM). Low concentrations of DON (12.5 μg/kg) and Zearalenone (5.5 μg/kg) were found in initial sampling, and no increase was detected during storage. Pellet length before bagging was 27.1 mm and decreased to 24.0 mm after storage, while dust percentage did not change (14.9%). These results indicated the feasibility of storing sunflower pellets in silo bags without quality deterioration.